Pelatihan Digital Marketing Dengan Imooji Sebagai Penunjang Kegiatan Promosi Dan Pemasaran UMKM di Bidang Kuliner - Nur Khasanah, Isnaini; Efriani, Dara Lita; Rahma, Nabilla Dwi; Putra, Ardian Prima (Yayasan Miftahul Ulum Sangatta Kutai Timur (KEP. MENKUMHAM RI No. AHU-0014779.AH.01.04.Tahun 2018) bekerjasama dengan Jurusan Tarbiyah STAI Sangatta Kab. Kutai Timur., 2024)
Digital marketing training with imooji is an initiative that aims to develop the knowledge and skills of MSME business actors in promoting products using digital promotional media. The method used in this service activity uses the socialization method and practice of making imooji. As a result of this training, business actors can make good use of digital promotional media. In this training, participants are invited to explore the potential of imooji as a creative tool that can increase visual appeal and customer interaction in the digital world. Imooji not only creates a pleasant impression, but can also be a key element in communicating the value of brands and culinary products to the target market. Through this training, MSME players are expected to be able to optimize their digital presence to increase visibility, increase customer engagement, and ultimately, increase sales of their culinary products.